Effectiveness of an add-on brief group behavioral activation treatment for depression in psychiatric care: a randomized clinical trial - Haakana, Riikka; Rosenström, Tom; Parkkinen, Lauri; Tuomisto, Martti T.; Isometsä, Erkki (Frontiers in Psychiatry, 2024)
Objective Behavioral activation (BA) is an effective treatment for depression. We investigated the effectiveness of add-on group-format BA and peer support (PS) with treatment as usual (TAU) in a registered randomized clinical trial in psychiatric outpatient settings (ISRCTN10647845). Methods Adult outpatients (N = 140) with major depressive disorder (MDD) and Patient Health Questionnaire (PHQ-9) score ≥10 were randomized into a) group BA, consisting of eight 90-minute weekly group sessions plus TAU; b) group PS, including eight 90-minute weekly group sessions plus TAU; or c) TAU alone. The primary outcome was a within-individual change in PHQ-9 score between baseline and 8 weeks. Secondary outcomes were 1) response, 2) remission, and 3) functional impairment at 8 weeks, plus 4) change in PHQ-9 at 6 months. Results Of the randomized patients, 100 (71.4%) completed treatments, including 29/45 (64.4%) patients in the BA group, 39/49 (79.6%) in the PS group, and 32/46 (69.6%) in the TAU group. By 8 weeks, PHQ-9 scores declined most in the TAU group [BA −0.28 (95% CI −2.48, 1.92), PS −0.58 (−2.09, 0.94) vs. TAU −3.32 (−5.21, −1.44); group-difference test, p = 0.034]. The secondary outcomes in the BA or PS arms did not significantly differ from those in TAU. Videotaped sessions revealed marked variation in briefly trained therapists’ adherence to the treatment manual. Conclusions In this randomized trial, the effectiveness of treatments with the added BA and PS groups did not exceed that of TAU alone. The preconditions in which brief BA or PS group interventions benefit outpatients with depression in psychiatric settings warrant critical investigation.